A Review of Design and Evaluation Practices in Mobile Text Entry for Visually Impaired and Blind Persons - Andreas Komninos; Vassilios Stefanis; John Garofalakis (Multimodal Technologies and Interaction, 2023)
Millions of people with vision impairment or vision loss face considerable barriers in using mobile technology and services due to the difficulty of text entry. In this paper, we review related studies involving the design and evaluation of novel prototypes for mobile text entry for persons with vision loss or impairment. We identify the practices and standards of the research community and compare them against the practices in research for non-impaired persons. We find that there are significant shortcomings in the methodological and result-reporting practices in both population types. In highlighting these issues, we hope to inspire more and better quality research in the domain of mobile text entry for persons with and without vision impairment.